ISLAMIC CURRICULUM MANAGEMENT AT PONDOK PESANTREN SALAFIAH BAITUL RAFKI AS-SA'DIYAH TALU TALAMAU DISTRICT PASAMAN BARAT - Refinal Refinal; Ahmad Lahmi; Mahyudin Ritonga (Profetika: Jurnal Studi Islam, 2021)
This study aims to illustrate how the management of Islamic curriculum in Salafiah boarding schools, this goal is based on the reality that the Islamic curriculum in each private educational institution has a difference between each other, this is because every manager of educational institutions, especially boarding schools have the authority to manage the curriculum. The methods used in this research are qualitative, research data sources of pondok pesantren leaders, representatives of curriculum fields, teachers in boarding schools are selected puvosif, data collection techniques used are observation, interviews and documentation studies, data analyzed with an interactive approach. Based on the results of the research it is known that the management of the curriculum in salafiah boarding school Baitul Rafki As-Sa'diyah Talu is: 1) islamic curriculum planning is dominated by the results of thought and desire of the leadership of islamic boarding schools, 2) the implementation of islamic curriculum in the boarding school is carried out all human resources in accordance with the direction of the curriculum representative, 3) Evaluation of the curriculum in this boarding school is not carried out in accordance with the demands of the changing times.